Control of the microsporidian parasite Nosema ceranae in honey bees (Apis mellifera) using nutraceutical and immuno-stimulatory compounds. - Daniel Borges; Ernesto Guzman-Novoa; Paul H Goodwin (PLoS ONE)
Nosema ceranae is a microsporidian parasite that causes nosemosis in the honey bee (Apis mellifera). As alternatives to the antibiotic fumagillin, ten nutraceuticals (oregano oil, thymol, carvacrol, trans-cinnmaldehyde, tetrahydrocurcumin, sulforaphane, naringenin, embelin, allyl sulfide, hydroxytyrosol) and two immuno-stimulatory compounds (chitosan, poly I:C) were examined for controlling N. ceranae infections. Caged bees were inoculated with N. ceranae spores, and treatments were administered in sugar syrup. Only two compounds did not significantly reduce N. ceranae spore counts compared to the infected positive control, but the most effective were sulforaphane from cruciferous vegetables, carvacrol from oregano oil, and naringenin from citrus fruit. When tested at several concentrations, the highest sulforaphane concentration reduced spore counts by 100%, but also caused 100% bee mortality. For carvacrol, the maximum reduction in spore counts was 57% with an intermediate concentration and the maximum bee mortality was 23% with the highest concentration. For naringenin, the maximum reduction in spore counts was 64% with the highest concentration, and the maximum bee mortality was only 15% with an intermediate concentration. In the longevity experiment, naringenin-fed bees lived as long as Nosema-free control bees, both of which lived significantly longer than infected positive control bees. While its antimicrobial properties may be promising, reducing sulforaphane toxicity to bees is necessary before it can be considered as a candidate for controlling N. ceranae. Although further work on formulation is needed with naringenin, its effect on extending longevity in infected bees may give it an additional value as a potential additive for bee feed in honey bee colonies.